2013
DOI: 10.1515/jbcpp-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective activity of Cocculus hirsutus leaf extract in 5/6 nephrectomized rat model

Abstract: The results indicate that C. hirsutus has strong nephroprotective activity. However, further scrutiny is essential for isolation and characterization of the active components that can be employed to allay various human maladies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The nephroprotective properties (Gadapuram et al, 2013) and mosquito adulticidal activity against the malarial vector, Anopheles subpictus (Elango et al, 2011) have been reported. Ethanol extract and crude alkaloidal fraction have significant antimicrobial activity against Gram-positive and Gramnegative bacteria and the activity is found to be concentration dependent (Nayak & Singhai, 2003).…”
Section: Cocculus Hirsutusmentioning
confidence: 99%
“…The nephroprotective properties (Gadapuram et al, 2013) and mosquito adulticidal activity against the malarial vector, Anopheles subpictus (Elango et al, 2011) have been reported. Ethanol extract and crude alkaloidal fraction have significant antimicrobial activity against Gram-positive and Gramnegative bacteria and the activity is found to be concentration dependent (Nayak & Singhai, 2003).…”
Section: Cocculus Hirsutusmentioning
confidence: 99%
“…Hence the only option remains folk medicines like Coccolus hirsutus, Muraya coignii, Anogiessus latifolia and many more. Now a days more emphasis is given to have better health instead of taking medicine, hence the use of Nutraceuticals is also increased [45][46][47]. Some herbal drugs which can be used as nutraceuticlas are Typha angustifolia and Typha latifolia, wheat grass, Piper betle, Bamboo etc [48][49][50][51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%